Is gender an issue in lifestyle-related diseases among adult Filipinos? (2002)
This study compared the prevalence of lifestyle-related disease conditions (e.g., hypertension, obesity, etc.) between males and females, randomly selected adults aged 20 years and over, using body mass index (BMI), waist-hip ratio (WHR), blood glucose, total cholesterol, LDL-cholesterol level, HDL-cholesterol level, triglyceride level, and blood pressure as parameters. The proportion of overweight and obese individuals are significantly higher among females than among males. Overnight females accounted for 18.9% and overweight males, 14.9% of the subjects. Furthermore, 4.4% of the females and 2.1% of the males are obese. Android or upper body obesity is more prevalent among (39.5%) than males (7.9%). There is no difference between the sexes in hypercholesterolemia and hypoglycemia, with prevalence of 4%. The high LDL-cholesterol level is almost the dame for both female and male subjects. High triglyceride level (400 mg/dL) is more pronounced among males (1.4%) than females (0.1%). The prevalence of overweight, total obesity, high waist circumference, and high waist-hip-ratio are higher among females than males. There are no significant differences observed between sexes for blood lipids.
Keywords: Lifestyles and health; Health--Sex differences